Non-Metallic Modified Thermal Barrier Coatings - Badalyan, A. O.
The radiation resistance and optical properties of zinc and zirconium silicate doped with cerium ion obtained by the hydrothermal microwave method are investigated. To study the radiation resistance of materials, the samples were irradiated with electrons energy of 4 MeV and a dose of 1016 el/cm2. X-ray diffraction (XRD) technique was used to characterize the phase composition of materials. To study the optical properties of materials, photoluminescence spectra were studied. Using the comparative section method, the thermal conductivity of the materials was measured. The results show that thermal barrier coatings made of cerium-doped zinc and zirconium silicate can be excellent candidates for use in space crafts and not only.
Keywords: Physics